2014
DOI: 10.2308/accr-50879
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Judgment: The Effects of Asset Impairment Reversibility and Cognitive Dissonance on Future Investment

Abstract: This paper examines how the reversibility of the accounting effect of asset impairments affects managers' investment decisions. We conduct two experiments in which participants act as CEO of a multi-division electronics company that suffers a large asset impairment at one of the divisions. Drawing on prior psychology research involving cognitive dissonance and decision reversibility, we predict and find that managers who are responsible for the decision to record the asset impairment invest more in the impaire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
1
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(27 citation statements)
references
References 27 publications
1
22
1
3
Order By: Relevance
“…In line with other recent top journal contributions studying psychology-related mechanisms relevant to the behavior of accounting and finance professionals (e.g., Chang et al, 2016;Emett & Nelson, 2017;Kumar, 2010;Rennekamp et al, 2015), we test and find support for our two hypotheses via an experimental setting using 289 business graduate students. Although the participants are not professional financial analysts, they do possess important analyst characteristics, such as knowledge of financial accounts and the limitations pertaining to earnings predictability.…”
Section: Introductionsupporting
confidence: 80%
“…In line with other recent top journal contributions studying psychology-related mechanisms relevant to the behavior of accounting and finance professionals (e.g., Chang et al, 2016;Emett & Nelson, 2017;Kumar, 2010;Rennekamp et al, 2015), we test and find support for our two hypotheses via an experimental setting using 289 business graduate students. Although the participants are not professional financial analysts, they do possess important analyst characteristics, such as knowledge of financial accounts and the limitations pertaining to earnings predictability.…”
Section: Introductionsupporting
confidence: 80%
“…Therefore, participants recruited through MTurk are an appropriate proxy of retail investors, once appropriate screening procedures are implemented. Notable studies in accounting that have used MTurk participants include Koonce et al [22], Rennekamp [4], and Rennekamp et al [23].…”
Section: Participantsmentioning
confidence: 99%
“…Incorrect CGU grouping, and their negative impact on overall goodwill valuation, has also been pointed out by Carlin et al [56], Carlin et al [57], Linnenluecke et al [58]. Rennekamp et al [59] proved that managers aim to maintain a positive self-image with their decisions. Giner and Pardo [30] suggested that recording asset impairment is caused by managers' unethical behaviours, derived from the avoidance of earnings surprises when they have a worse financial year than they expected.…”
Section: Asset Impairment As An Opportunity For Earnings Managementmentioning
confidence: 89%